Babad Bakalan Sebuah Data Baru Bagi Sejarah Indonesia Kuno - nfn. Masyhudi (Balai Arkeologi Yogyakarta, 1994)
Stories about saints are generally found in various historiographical texts or constitute local history. However, the correctness of the text is still questionable. Babad Bakalan is a text that as a whole reveals matters of a historiographical or local history, and the manuscript is reliable. On this occasion, a paper will be presented based on new data obtained in research on the Islamic Mataram Settlement and Transportation Route in Wonogiri Regency.